Study of Carbohydrates from the Seeds, Leaves and Kernel of Sterculia guttata Roxb. - R. Katade, Sushama; R. Deshmukh, Madhavi; M. Shah, Sapana; R. Deshpande, Nirmala (Asian Journal of Chemistry, 2016)
Carbohydrate analysis of the seeds, leaves and kernel of Sterculia guttata showed the presence of D-lactose, L-sorbose, D-arabinose, L-rhamnose, D-glucose, maltose and D-fructose, whereas L-rhamnose and D-fructose are common in all three parts of the plant, i.e., seeds, leaves and kernel.